Tourist Satisfaction with The Services Provided By The Hotel Industry Of Chennai – A Study (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study intends to access the extent of tourist satisfaction with service quality, staff attributes and hotel dimensions specifically related to the hotel industry of Chennai. In this study a sample of 50 tourists staying in the hotels of Chennai were studied. Collected data were analysed using frequency, t-test and One-way ANOVA. Frequency was used to gather data regarding demographic profile of tourist, factor analysis was applied in order to cluster varied items related to service provided by hotel and its various dimensions, t-test was applied to find out if their exist significant differences in service quality and between two group mean and One-way ANOVA ‘f’ test was applied to find out significant differences between more than two groups of an independent variable. The findings of the study revealed popularity of Chennai as a tourist destination and satisfaction of tourist with staff attributes but revealed just average satisfaction with the service quality. So the statistical findings supported a need of improvement in service quality and hotel dimension for a higher satisfaction among guest. Service quality is critical factor for the success of any business. Also there is also a dire need to focus on amenities within hotel premises and improvement in food service and hotel ancillary services. The outcome of the study will direct the hotel industry of Chennai to focus and improve on important aspect like service quality, hotel amenities and adopt customer oriented philosophy which is vital for retaining customer and long term sustenance of the industry.